The quest for population‐level cancer recurrence data; current deficiencies and targets for improvement. Issue 6 (17th February 2015) - In, Haejin; Simon, Cassie A.; Phillips, Jerri Linn; Posner, Mitchell C.; Ko, Clifford Y.; Winchester, David P.
Abstract : Background: Cancer recurrence is a critical outcome in cancer care. However, population‐level recurrence information is currently unavailable. Tumor registries provide an opportunity to generate this information, but require major reform. Our objectives were to (1) determine causes for variability in collection of recurrence, and (2) identify targets for intervention. Methods: On‐site interviews and observations of tumor registry follow‐up procedures were conducted at Commission on Cancer (CoC) accredited hospitals. Information regarding registry resources (caseload, staffing, chart availability), follow‐up methods and perceived causes for difficulty in obtaining recurrence information was obtained. Results: Seven NCI/academic, 5 comprehensive community and 2 community centers agreed to participate. Hospitals were inconsistent in their investigation of cancer recurrence, resulting in underreporting of rates of recurrence. Hospital characteristics, registry staffing, staff qualifications and medical chart access influenced follow‐up practices. Coding standards and definitions for recurrence were suboptimal, resulting in hospital variability of recurrence reporting. Finally, inability to identify cases lost to follow‐up in collected data prevents accurate analysis of recurrence rates. Conclusion: Tumor registries collect varying degrees of recurrence information and provide the underpinnings to capture population‐level cancer recurrence data. Targets for intervention are listed, and provide a roadmap to obtain this critical information in cancer care. J. Surg. Oncol. 2015 111:657–662 . © 2015 Wiley Periodicals, Inc.